Peningkatan Produktivitas Ikan Lele Menjadi Nugget Untuk Meningkatkan Kesejahteraan Petambak Lele - Diah Anugrah Dipuja; Kenny Indah Lestari; Desi Nofriyanni; St. Aisyah Roesman; Icha Wismiati; Munani Salwa; Natalia Siregar; Rifani Indra Putra; Amalia Febriani; Hesron Leonardo Sihombing; Reza Asrian (Unri Conference Series: Community Engagement, 2021)
The large number of catfish farmers in Dumai Timur District, especially in Tanjung Palas Village, makes the supply of catfish abundant, causing the price of catfish at harvest time to be very cheap and unable to meet operational costs. This is also because the results of catfish farming are directly sold to consumers or distributors. For this reason, a community service program is carried out which aims to help increase people's income by utilizing the results of catfish farming. The method used in this community service program is to provide socialization of processing catfish into nuggets to catfish farmers by using video facilities. The socialization activity was successfully implemented and accepted by catfish farmers, namely the Palas Jaya group in Tanjung Palas Village. The result of this service is that farmers get knowledge and information in processing their catfish cultivation which can be a solution to increase added value to catfish which was previously priced cheaply at harvest.